The Relationship Between Organizational Learning Capabilities And Job Satisfaction In Tehran Hospitals - Edris Kakemam; Afife Irani; Mobin Sokhanvar; Amin Akbari; Hossein Dargahi (Tehran University of Medical Sciences, 2016)
Background and Aim: Scientific and technological developments have promoted the status of organizational learning as a reasonable way to deal with the present changing circumstances. The development of organizational learning improves the performance of employees, and makes them feel satisfied. The aim of this study is to investigate the relationship between job satisfaction and organizational learning capabilities among the employees of Tehran hospitals. Materials and Methods This descriptive, analytical study was conducted among 290 employees in 2014 in Tehran hospitals. For data collection, a three-part questionnaire (including demographic characteristics, Gomez`s Organizational Learning Capability Questionnaire and Minnesota Job Satisfaction Questionnaire) was given to 290 employees. Data were analyzed using the SPSS-20 software with Spearman test. Results: Mean scores of organizational learning capability and job satisfaction were (3.03± 0.61) and (2.8± 0.61), respectively. Among the dimensions of organizational learning capability, the highest score pertained to systematic perspective (3.29± 0.78); regarding job satisfaction, the highest score was related to organizational climate (3.23± 0.1). The results showed that there was a significant correlation between the dimensions of organizational learning capability and job satisfaction. Also, a significant correlation was observed between organizational learning capabilities and job satisfaction. Conclusion: Organizational learning improves the performance of employees and is positively correlated with their satisfaction. Also, employee satisfaction is one of the factors affecting their performance. Therefore, managers can make employees satisfied and develop their organization through improving organizational learning.